WEAVING HERITAGE: THE ART AND LEGACY OF KUPPADAM PATTU SAREES IN ANDHRA PRADESH - Anisha, Sagiraju Lakshmi; Kumar, Rajesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Kuppadam Pattu sarees, renowned for their exquisite craftsmanship and intricate weaving techniques, represent a significant cultural artifact of Andhra Pradesh. This paper explores and documents the traditional methods involved in creating these sarees, their unique features, and their historical and contemporary relevance. Through an in-depth examination of the weaving process, including the unique interlocking weft technique known as ’Kupadam,’ the paper highlights the meticulous craftsmanship that goes into each saree. This study delves into the socio-cultural importance of Kuppadam Pattu sarees, tracing their evolution and enduring presence in Indian fashion. By shedding light on the artistry and heritage of these textiles, the research underscores the necessity of preserving and promoting traditional handloom practices. Ultimately, this paper seeks to support artisans, support sustainable fashion, and promote a more profound gratitude for India’s rich textile heritage.